At the threshold of liberty : women, slavery, and shifting identities in Washington, D.C. - Nunley, Tamika (John Hope Franklin series in African American history and culture., 2021)
"At the center of a nation founded on the premise of liberty, nineteenth-century Washington D.C. was governed by federally-appointed commissioners who enacted black codes that confined the social and physical mobility of black Americans in the District, placing black women at the bottom of a broader social schema ordered by race and gender. At the threshold of liberty examines the ways that African American women-enslaved, fugitive, freedwomen, and refugee-lived, survived, and made claims to liberty from the founding of the nation's capital to the American Civil War, focusing on their strategies of self-making in the contexts of slavery and fugitivity in courts, schools, streets, and government. These liberty claims were constant reminders of the contradiction between bondage and the symbolism of the nation's capital as the centerpiece of the new republic and its ideals"--